The use of the forced repetitions method on the strength training to increase the hormonal and neuromuscular responses - Frois, Rafael Rodrigues de Sousa (2012)
This bibliography review analyses scientific articles about the theme Forced Repetitions, exploring the hormonal and neuromuscular responses generated with the use of this method comparing to other training systems. Were selected studies that research the acute and chronic physiological responses generated by the use of the Forced Repetitionsmethod, accessed through the Medline and Scielo databases. The search results in 5 articles that obey the inclusion criterion, being only 1 relationated to chronic responses. The research shows that the referred method produces higher elevations in the concentration of the hormones Testosteron, GH and Cortisol in a acute way when compared with conventional training systems. Beyond this, the included studies shows a bigger reduction in the maximum isometric strength after training with Forced Repetitionscomparing with traditional methods, as well as the extension in the activity time of the CK protein after training with Forced Repetitions. The studies also shows that the total loading applied to the muscle is bigger in the training with Forced Repetitionsthan with conventional training systems. This data reinforce the efficiency of the FR method in generate acute hormonal responses. This responses, in a chronic way, can promote bigger results relationated with strength gains and hypertrophy, what would make the Forced Repetitionsmethod capable of promote better responses to the strength training than a conventional training protocol.